An analysis of teachers’ digital competences in the province of Misiones: the challenge of the new literacy - Sánchez-Cruzado, Cristina; Bonetti, Sandra; Sánchez-Compaña, María Teresa; Campión, Raúl Santiago (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2021)
This paper is part of one of the lines of research and development defined in a collaboration agreement between the province of Misiones, Argentina and the University of La Rioja, Spain. The main objective is the analysis of digital literacy in both teachers and students to establish a starting matrix and check its subsequent evolution. The most relevant results obtained in a study carried out between 2019 and 2020 in which 1,422 teachers from Misiones of all educational levels participated are presented. To achieve this goal, an analysis on the self-perception of the digital skills is carried out. This work is implemented by taking as reference the common framework of digital competences of the INTEF and using, for the collection and analysis of the data, the ACDC questionnaire. Results show a low perception of their own digital competences in most of the areas analyzed, especially in those related to content creation. Finally, some teacher training actions are proposed focusing on the necessary alignment of digital resources and didactic methodologies.